Moderating effects of net export and exchange rate on profitability of firms: a two-step system generalized method of moments approach - Hussain, Sarfraz; Ali, Rosalan; Abdul Latiff, Ahmed Razman; Fahlevi, Mochammad; Aljuaid, Mohammed; Saniuk, Sebastian (Informa UK, 2024)
This study examines the effects of exchange rate and net exports on manufacturing enterprises’ profitability on the Pakistan Stock Exchange (PSX). When activity-based accounting is examined using panel data techniques, the main objective is to examine the direction and magnitude of the moderating influence of exchange rate fluctuations on net exports and the return on assets. We employed 249 manufacturing companies on the Pakistan Stock Exchange from 1999 to 2019. The Pakistani economy used a multicurrency system, using the Generalize Method of Moment (GMM) regression analysis system. The number of debtors’ days, creditors’ days, the cash conversion cycle, and the company’s return on assets all link favorably. Inventory turnover days, financial leverage, net exports, exchange rate, and return on assets are all negative. The Size and age of a business have a significant positive association with profitability but a negative relationship with Return on Assets (ROA). This study suggests that activity-based accounting improves company performance. Recognizing interdependence, net exports owing to currency rate depreciation have adverse effects. Managers may construct an appropriate measure to control activity-based working according to forex market symptoms and when macro-economic factors modify micro-economic policies’ behavior to increase ROA. Hence, debtors need to be paid early, and payables need to be paid late, but in these cases, the financial management should improve the return on assets.